(untitled) (Third Sector Social Economic Review, 2019)
This study aims to investigate the satisfaction level of the people who bought life insurance from insurance companies. People who bought life insurance in the city of Ankara are participants of the study. Mankind has been constantly faced with various dangers since the early ages. Accident, illness, death, unemployment, fire, flood etc. The risks of loss of life, property and property are some of the risks encountered in every period of life. As in all sectors, it is necessary to analyse the opinions and expectations of the customers in order to be permanent in insurance business. These analyses are important in terms of meeting customer satisfaction, providing solutions for the problems of the customers, and meeting the needs of the customers. Life insurances are the types of insurances which are about human life and which include protection and saving functions. They are long-term fixed benefit and fixed sum insurances. Life insurances are usually long-term interest or sum insurances, the subject of which is human life. In the study, local and foreign sources in the literature which consist of insurance industry, the structure of the insurance industry, types of insurance and the institutions in the insurance sector, and life insurance which is one of the leading types of insurance are broadly used. The result of this study hopes to contribute in general to life insurance industry, insurance agencies in terms of the measurement of customer satisfaction and insurance sector.